2021
DOI: 10.21037/tcr-20-2813
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D modulation and microRNAs in gastric cancer: prognostic and therapeutic role

Abstract: Gastric adenocarcinoma arises after a complex interaction between the host and environmental factors. Tumor location and TNM are the tools that currently guide treatment decisions. Surgery is the only curative treatment, but relapse is common. After relapse or advanced staged disease survival is poor and systemic treatment has modestly improved survival. An association between sun exposure, vitamin D status and gastric cancer (GC) incidence and mortality has been reported. The molecular differences of the hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 151 publications
(219 reference statements)
0
6
0
Order By: Relevance
“…Moreover, a similar expression gene pattern was found between 25(OH)D 3 and 1α,25(OH) 2 D 3 either in the transcriptome of PBMCs and LNCaP [39,40,57]. Recently, it has been demonstrated that 1,25(OH) 2 D 3 exerts regulatory effects on microRNA expression and long non-coding RNAs, potentially serving as a potential anticancer mechanism [103,104]. In this regard, no evidence has been established for the 25(OH)D 3 -induced regulation of these classes of non-coding RNA so far.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, a similar expression gene pattern was found between 25(OH)D 3 and 1α,25(OH) 2 D 3 either in the transcriptome of PBMCs and LNCaP [39,40,57]. Recently, it has been demonstrated that 1,25(OH) 2 D 3 exerts regulatory effects on microRNA expression and long non-coding RNAs, potentially serving as a potential anticancer mechanism [103,104]. In this regard, no evidence has been established for the 25(OH)D 3 -induced regulation of these classes of non-coding RNA so far.…”
Section: Discussionmentioning
confidence: 56%
“…Vitamin D may modulate the expression of some miRNAs that are deregulated in gastric cancer cells. In this mechanism, vitamin D reduces chemoresistance at the cellular level [36]. Our review found that patients with gastric cancer have vitamin D deficiency, with reported rates ranging from the initial 36.67% of patients [15] up to 89% [21].…”
Section: Discussionmentioning
confidence: 84%
“…In patients with gastric cancer, it was also the vitamin D metabolite investigated that mattered, as demonstrated by Rino Y et al al, who found that although 1,25(OH) 2 D may be normal in gastric patients, the level of the most active metabolite, 25(OH)D, may remain below the normal range in a significant number of them (31.8%) [24]. However, there is still no single study that would support with strong evidence that vitamin D supplementation could result in a decrease in gastric cancer incidence rate neither in the general population nor in relapsed patients [36], and the deficiency reported initially in gastric cancer patients remains consistent with the general global population deficiency, estimated at 37.3% (circulating concentrations of 25(OH)D below 20 ng/mL) [37].…”
Section: Discussionmentioning
confidence: 99%
“…It regulated gene expression by combining with the complementary site of 3′UTR to destroy its transcriptional stability [ 34 , 35 ]. Its expression regulated the expression of a variety of genes, which was crucial to the occurrence and development of gastric cancer [ 36 , 37 ]. In previous studies, miR-379-5p was overexpressed in most tumors.…”
Section: Discussionmentioning
confidence: 99%